2017
DOI: 10.1177/0146167216684124
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just Sex

Abstract: Positive interpersonal interactions such as affection are central to well-being. Sex is associated with greater individual well-being, but little is known about why this occurs. We predicted that experienced affection would account for the association between sex and well-being. Cross-sectional results indicated that affection mediated the association between sex and both life satisfaction (Study 1) and positive emotions (however, among men only in Study 2). In Study 3, an experience sampling study with 106 du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(16 citation statements)
references
References 59 publications
(88 reference statements)
1
15
0
Order By: Relevance
“…High and expected associations (Cooper et al, 1998 ; Armstrong and Reissing, 2015 ; Gravel et al, 2016 ; Jardin et al, 2017 ) between relational status and sexual motivations were found, such that participants who had no partner presented higher scores than those who had a partner for aversive motivations, such as those of coping and peer pressure, and lower scores in appetitive motivations, such as those of intimacy. It is considered that having a partner acts as a protective factor and has positive consequences for well-being (Debrot et al, 2017 ), as can be seen in this study, with higher scores in self-esteem as a sexual partner and satisfaction with sex life in people who had a partner.…”
Section: Discussionsupporting
confidence: 64%
“…High and expected associations (Cooper et al, 1998 ; Armstrong and Reissing, 2015 ; Gravel et al, 2016 ; Jardin et al, 2017 ) between relational status and sexual motivations were found, such that participants who had no partner presented higher scores than those who had a partner for aversive motivations, such as those of coping and peer pressure, and lower scores in appetitive motivations, such as those of intimacy. It is considered that having a partner acts as a protective factor and has positive consequences for well-being (Debrot et al, 2017 ), as can be seen in this study, with higher scores in self-esteem as a sexual partner and satisfaction with sex life in people who had a partner.…”
Section: Discussionsupporting
confidence: 64%
“…Future work may also use emojis to further connect research in social psychology, communications, and relationship science. Researchers continue to uncover the role of communication in people’s romantic and sexual lives [30, 31], and this extends to the importance of non-verbal behaviors in relationships, such as affection and positive affect [32]. Indeed, positive text messages to a partner have been associated with increased relationship satisfaction [33].…”
Section: Discussionmentioning
confidence: 99%
“…Relative to sexual intimacy, research shows that frequent and positive communication play a pivotal role in nurturing satisfying sexual relationships for couples (Leistner and Mark, 2020). Positive and affectionate communication has also been linked to more frequent sexual contact (Willoughby et al, 2014;Debrot et al, 2017;Schoenfeld et al, 2017). In terms of finances, research has shown that more positive financial communication can improve couple relationship quality (Zimmerman and Roberts, 2012), which may explain why prosocial communication has also been identified as a preventative measure against potential economic distress (Conger et al, 1999).…”
Section: Communicationmentioning
confidence: 99%